Redesign Layout of Production Facilities Using Systematic Layout Planning and ARC Methods at UMKM Bill Bakerykoe - Sekarningtyas, Hikmah; Faza, Iqbal; Kafidzin, Rohmad; Prasetyo, Iwan (Jurnal Logistik Indonesia, 2024)
Bill Bakerykoe is one of the UMKM operating in the food sector in Kudus, with the main production being Donat and Roti Manis. Based on observations, UMKM do not yet have a good work area arrangement. In carrying out bread production activities, using the current layout of production facilities, it was found that the arrangement of the work areas was not in accordance with the sequence of the production process flow from the initial process to the final process. Thus, there was repetition in passing through production areas that should not have been time to pass. The work stations observed were from the location of the raw material warehouse, production machines, to the product packaging area. This research aims to provide proposals for the layout of new production facilities that is appropriate and more efficient, and can eliminate repetitive activities that can waste a lot of time, by minimizing the total production distance. The research method used is Systematic Layout Planning (SLP) which starts from preparing a production route sheet, production process map, creating an ARC (Activity Relationship Chart), redesigning the layout, stages of analyzing the results, then conclusions and suggestions. The results of the research were changes to the layout of 7 work areas including the raw material area 1 (A), the leftover materials area (C), the equipment warehouse area (D), the dough molding area (F), the dough frying area (G), the Donut WIP (J), and equipment washing area (O). As for the comparison of the total production distance in the initial layout and the improved layout, the results showed that the new layout can reduce the total production distance by 16.4 meters.